2017
DOI: 10.3389/fpls.2017.00063
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Ectopic Expression of CoWRI1, an AP2/EREBP Domain-Containing Transcription Factor from Coconut (Cocos nucifera L.) Endosperm, Changes the Seeds Oil Content in Transgenic Arabidopsis thaliana and Rice (Oryza sativa L.)

Abstract: Coconut (Cocos nucifera L.) is a key tropical crop and a member of the monocotyledonous family Arecaceae (Palmaceae). Few genes and related metabolic processes involved in coconut endosperm development have been investigated. In this study, a new member of the WRI1 gene family was isolated from coconut endosperm and was named CoWRI1. Its transcriptional activities and interactions with the acetyl-CoA carboxylase (BCCP2) promoter of CoWRI1 were confirmed by the yeast two-hybrid and yeast one-hybrid approaches, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…Our result suggested that the expression of EuWRI1 might be seed‐specific in E. ulmoides . This result was agreed with previous report that CoWRI1 was highly expressed in endosperm, whereas its expression was lower in other plant tissues . The expression pattern of EuWRI1 in different seed developmental stages with the treatment of GA3 or PAC was also studied in this study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our result suggested that the expression of EuWRI1 might be seed‐specific in E. ulmoides . This result was agreed with previous report that CoWRI1 was highly expressed in endosperm, whereas its expression was lower in other plant tissues . The expression pattern of EuWRI1 in different seed developmental stages with the treatment of GA3 or PAC was also studied in this study.…”
Section: Discussionsupporting
confidence: 93%
“…8,38 The CoWRI1 overexpression effect on fatty acid content in transgenic A. thaliana seeds significantly differed from the effect in transgenic rice seeds. 17 These results suggested that the transcriptional effects of WRI1 might depend on the origin of the transgene and the transgene recipient as well as the position effect of transgene integration into the host genome.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…If conserved, knowledge about lipid pathways can be transferred between plant species. The oil content in the seeds of A. thaliana mutants lacking WRINKLED1 ( WRI1 ), a key master regulator of FA biosynthesis in higher plants, was restored with the respective orthologs from rapeseed (Liu et al ., ), Camelina sativa L. (An et al ., ), maize (Pouvreau et al ., ), oil palm (Ma et al ., ) and coconut (Sun et al ., ). In maize, WRI1a and WRI1b encode transcription factors of the APETALA2/ethylene‐responsive element‐binding (AP2/EREB) family that increase FA content in seeds and are co‐expressed with glycolytic enzymes and genes involved in FA and TAG biosynthesis in the kernel (Pouvreau et al ., ).…”
Section: Introductionmentioning
confidence: 97%